2016
DOI: 10.1007/s00540-016-2285-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the presence of postoperative headache in elective surgery patients: a prospective single center cohort study

Abstract: Female gender, sevoflurane, smoking and intraoperative hypotension were documented as independent risk factors for postoperative headache. In patients with no previous history of headache, caffeine consumption was an additional independent factor for postoperative headache, while smoking revealed no association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 25 publications
6
20
1
Order By: Relevance
“…Postoperative headache (POH) is a common complication after surgical procedures, associated with increased morbidity, prolonged hospital stay, reduced quality of life, and additional economic burden (4)(5)(6)(7)(8)(9)(10). The incidence of POH reported in the literature varies substantially after different types of surgery (4,6,9,(11)(12)(13)(14)(15)(16)(17). Currently, some studies have been carried out to identify possible predictors for the occurrence of POH in patients undergoing craniotomy, general, spinal, orthopedic, gynecologic, and ear-nose-throat procedures (6,13,16,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative headache (POH) is a common complication after surgical procedures, associated with increased morbidity, prolonged hospital stay, reduced quality of life, and additional economic burden (4)(5)(6)(7)(8)(9)(10). The incidence of POH reported in the literature varies substantially after different types of surgery (4,6,9,(11)(12)(13)(14)(15)(16)(17). Currently, some studies have been carried out to identify possible predictors for the occurrence of POH in patients undergoing craniotomy, general, spinal, orthopedic, gynecologic, and ear-nose-throat procedures (6,13,16,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Several related risk factors have been reported, such as age, female gender, previous history of headache, and anaesthetic drugs (13,18,22). However, there are only few reports available about the development of POH after cardiac surgery, and basically it's just used as a secondary outcome (23).…”
Section: Introductionmentioning
confidence: 99%
“…Migraine was individually associated with postsurgical 30-day readmission for both of these types of pain. It is well known that patients with migraine are vulnerable in the perioperative phase with the headache occurring within hours and up to five days after surgery (2123). Our data confirm these findings and add the information that both headache and abdominal pain after surgery are a mechanism of readmission to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…There were 10 studies investigating the effect of caffeine peri-operatively and the development of post-operative headache [24][25][26][27][28][29][30][31][32][33] . Seven investigated caffeine withdrawal [24][25][26][27][28][29][30][31][32][33] and three studies administered oral caffeine to prevent post-operative headache [31][32][33] . Of the seven prospective studies investigating the effect of caffeine withdrawal, ve studies found caffeine withdrawal increased the incidence of post-operative headache [24][25][26][27][28][29][30][31][32][33] .…”
Section: Caffeine Use In the Peri-operative Periodmentioning
confidence: 99%
“…Seven investigated caffeine withdrawal [24][25][26][27][28][29][30][31][32][33] and three studies administered oral caffeine to prevent post-operative headache [31][32][33] . Of the seven prospective studies investigating the effect of caffeine withdrawal, ve studies found caffeine withdrawal increased the incidence of post-operative headache [24][25][26][27][28][29][30][31][32][33] . Three studies investigated the administration of caffeine to relieve post-operative headache [31][32][33] .…”
Section: Caffeine Use In the Peri-operative Periodmentioning
confidence: 99%